Application of Bamboo Material to the Characteristics of Residential Houses in the Tropics: Hideout Bali - Vania Lescha; Tessa Eka Darmayanti (Jurnal Arsitektur, 2022)
Global warming and climate change are challenges for the world community today. The construction of buildings and properties is one of the biggest contributors in producing carbon dioxide which causes global warming and climate change for the earth. Property development consumes a lot of energy starting from material processing to use and produces waste that pollutes the environment. Over time, the use of sustainable materials is one of the best solutions to reduce material waste that can be harmful to the environment. In this article the case study that will be discussed is Hideout Bali which is located in Bali. This house-shaped resort uses bamboo as the main material so that it is more environmentally friendly. The purpose of writing this journal article is to analyze the suitability of applying sustainable materials, especially bamboo, to the criteria for housing in tropical climates, case study: Hideout Bali. The research method used is a qualitative method by analyzing the application of one of the sustainable materials, namely bamboo, to the criteria for housing in Indonesia, which has a tropical climate. This study uses an exploratory literature method sourced from scientific study books, discussion forums on the internet and research articles on sustainable materials published online. This journal article is expected to be able to add insight and public awareness to better protect the environment by considering sustainable design.